2022
DOI: 10.1073/pnas.2206925119
|View full text |Cite
|
Sign up to set email alerts
|

Initial impressions of compatibility and mate value predict later dating and romantic interest

Abstract: Romantic first impressions seem to linger, but why? Few studies have investigated how romantic desire during initial interactions predicts later relational outcomes (e.g., later romantic interest, contact attempts) using a design that can tease apart different possible mechanisms (e.g., mate value, selectivity, compatibility). Across three speed-dating studies ( n = 559) with longitudinal follow-ups (including college and community samples, and a sample of men who date men), we investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…Future research should aim to disentangle and quantify the effects of general attractiveness and individual attractiveness preferences on attention. For example, a recent study on dating behavior 41 showed that both general and individual preferences uniquely contribute to date outcome, but whether this is also the case for attentional processes remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Future research should aim to disentangle and quantify the effects of general attractiveness and individual attractiveness preferences on attention. For example, a recent study on dating behavior 41 showed that both general and individual preferences uniquely contribute to date outcome, but whether this is also the case for attentional processes remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a large-scale study showed no evidence that different initial meeting contexts (e.g., bars, church, online) influence divorce rates 87 . In a speed-date context, it has been shown that first impressions, which are asserted by some to reflect short-term mate choice processes, still predict long-term romantic interest 41 . In conclusion, our findings should not be interpreted as the product of uniquely long- or short-term mate choice processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because initial impressions tend to linger: How individuals perceive each other when they first meet predicts how they think, feel, and behave towards each other in the future (Harris & Garris, 2008). In humans, first impressions (even based on short initial interactions) are especially important in the context of dating and romantic relationships, shaping who people pursue as romantic and/or sexual partners (Baxter, Maxwell et al, 2022; Eastwick et al, 2021; Reis et al, 2011). Studies in non‐human species have shown that initial impressions also play an important role in guiding social decisions and affective evaluations as well ( capuchins , squirrel monkeys , and dogs : Anderson et al, 2017; marmosets : Brügger et al, 2021; Kawai et al, 2019; ravens : Müller et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, most studies of mate choice (in both humans and nonhuman species) have been premised on the partner effect (i.e., mate value, sexual strategies, etc.). However, there is growing evidence (primarily from human studies) that compatibility also contributes to mate choice and relationship formation (e.g., see Baxter, Maxwell et al, 2022; Eastwick & Hunt, 2014; Eastwick et al, 2021; Zeevi et al, 2022), suggesting that partner and relationship effects may be competing factors that influence how humans (and potentially other pair‐bonding species) evaluate potential mates. For example, according to some evolutionary models of human mating (Eastwick et al, 2019; Hazan & Diamond, 2000), humans evolved to select mates that were genetically‐fit (partner effects) and that they were initially compatible with (relationship effects), as initial compatibility would likely translate to long‐term compatibility, and long‐term partnerships were necessary for mates to successfully rear their offspring (and also to ensure their own survival).…”
Section: Introductionmentioning
confidence: 99%